Yield surface derivation for a structural adhesive based on multiaxial experiments. (September 2022) - Wentingmann, Michael; Manousides, Nikolas; Antoniou, Alexandros; Balzani, Claudio
Abstract: Yield surface determination is an essential part of a material characterization, enabling the qualification of a suitable yield criterion. In the case of two-component, fiber-reinforced structural adhesives the manufacturing quality of the specimens is directly linked to the determination accuracy of the yield surface. Therefore, this work was based on specimens that have been optimized in a previous study utilizing a structural, epoxy-based adhesive designed for the manufacture of wind turbine rotor blades. This allowed for a precise identification of a yield locus in combined tension–torsion and compression–torsion experiments. A practical elasto-plastic shear stress correction was developed to account for the transition between elastic and plastic states. In addition, a scaling method of an elliptical yield locus fitting function is proposed to calculate equivalent stresses and strains. The obtained results are discussed regarding influences of viscoelasticity and are compared to existing yield criteria. Graphical abstract: Highlights: Yield surface determination for rotor blade bonding paste. Low uncertainties due to high quality specimens. Practical elasto-plastic shear stress correction for tubular specimens. Elliptical scaling of yield locus to calculate equivalent stresses and strains. Qualification of a yield criterion for structural adhesives.